Criminal Liability to The Persons Of Prostitution (Case Study Number.601/PID.B/2019/PN.SBY) - Pompy Polansky Alanda; Adhiem Widigdo; Parlindungan Tua Manullang; Ikhwa Nul Padli (Jurnal IUS Kajian Hukum dan Keadilan, 2019)
Since the localization Dolly closed by the Surabaya Mayor, obviously prostitutions practical are continuing secretly just like the one in the prostitution case by YEKNO. He was introduced AGUS with I MADE NILO for dating in HENKY house. The aim of this research are to analyze what are the criminal responsibilities towards the prostitution perpetrators and also to find out the criteria of pimp in prostitution. The research methods used in this study is normative law method with constitution approach, conceptual approach, and case approach. The results of this study indicate that YEKNO decided guilty based on Chapter 2 subsection (1) Undang-Undang Republik Indonesia No. 21 Year 2007 about Eradication Criminal Offence of Human Trafficking (UU PTPPO) by the judge verdict number 601/ Pid.B/ 2019/ PN.SBY which is what YEKNO did. YEKNO is not proved as pimp, because a pimp has a special criteria of role thus HENKY as a provide guilty based on Chapter 296 KUHP, beside that for I MADE NILOand AGUS were not guilty because no rules for their role.